Kompetensi Manajerial Kepala Madrasah Dalam Meningkatkan Profesionalisme Kinerja Guru Di Mas Al-Ittihadiyah Mamiyai Medan - Geniza Aidilla Syuaira; Abdul Fattah Nasution (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Managerial Competence of Madrasah Heads in Improving Teacher Performance Professionalism at Mas Al-Ittihadiyah Mamiyai Medan This study focuses on examining the managerial capabilities of leaders in accelerating the professionalism of educators at MAS Al-Ittihadiyah Mamiyai Medan. The method employed is a qualitative approach with a descriptive design. Data collection techniques include participatory observation, in-depth interviews, and documentation studies. Meanwhile, the analysis process was conducted through data reduction, systematic presentation, and conclusion verification. Field findings indicate that the planning and task distribution aspects by the madrasah leadership have been optimal. This is evidenced by the preparation of annual and semester work agendas and the allocation of teaching loads that consider the expertise of each teacher. In terms of capacity building, professional development is realized through routine forums, classroom visits for supervision, and the provision of motivational stimuli. Support for self-development is also provided through facilitating independent training via the Pintar Kemenag application. Regarding quality control, supervision and evaluation mechanisms operate continuously by monitoring attendance, the completeness of learning administration, and the quality of teaching-learning interactions in the classroom. Comprehensively, the managerial capacity of the madrasah leadership contributes significantly to enhancing the discipline, accountability, and professional quality of educators.